2020
DOI: 10.3389/fpsyt.2020.581598
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Depression Symptoms in COVID-19 Isolated Patients and in Their Relatives

Abstract: Background: While focusing on the management and care of COVID-19 patients, the mental health of these patients and their relatives is being overlooked. The aim of the current study was to measure anxiety and depression, and to assess their association with socio-demographic and pandemic-related stress factors in COVID-19 patients and their relatives during the initial stage of hospitalization. Methods: We assessed isolated hospitalized patients (N = 90) and their relatives (adults and children, N = 125) by ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 19 publications
5
60
0
2
Order By: Relevance
“…This study aimed to assess the depressive symptoms in patients with COVID-19 and to find out the associated factors with it. In sex distribution, men were more infected than women and it was in line with the findings of previous studies done in China [ 32 , 33 ], and Israel [ 34 ]. However, this finding was contrary to the results of the other studies conducted in the China [ 19 , 35 ] and Ecuador [ 36 ] stated that the sex distribution of patients with COVID-19 was not too different.…”
Section: Discussionsupporting
confidence: 91%
“…This study aimed to assess the depressive symptoms in patients with COVID-19 and to find out the associated factors with it. In sex distribution, men were more infected than women and it was in line with the findings of previous studies done in China [ 32 , 33 ], and Israel [ 34 ]. However, this finding was contrary to the results of the other studies conducted in the China [ 19 , 35 ] and Ecuador [ 36 ] stated that the sex distribution of patients with COVID-19 was not too different.…”
Section: Discussionsupporting
confidence: 91%
“…However, evidence on the nature of the association of resilience and psychological distress is still inconclusive [54][55][56] and more research is needed to identify effective interventions [53]. Dorman-Ilan et al [32] found that relatives who did not feel protected by the hospital might suffer from increased anxiety even one month after patients' discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Relatives of patients hospitalized with COVID-19 might be equally affected but evidence is scarce. The study of Dorman-Ilan et al [ 32 ] suggests that both isolated COVID-19 patients and relatives might suffer from similarly high levels of anxiety and depressive symptoms during the initial stage of hospitalization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the COVID-19 pandemic, a study of 1,210 respondents in China showed that 84.7% spent 20-24 h per day at home and experienced the rates of moderate to severe depression and anxiety of 16.5 and 28.8%, respectively (Wang et al, 2020). In addition, the relatives of COVID-19 patients suffered from high levels of anxiety due to feelings of insecurity and loss of a sense of control (Dorman-Ilan et al, 2020). Most Italian residents had higher levels of distress because of positive cases nearby, the prolonged lockdown and having to relocate (Di Giuseppe et al, 2020).…”
Section: Introductionmentioning
confidence: 99%